A descriptive study of experience of laparoscopic repair of retrocaval ureter in a tertiary care institute in Eastern India - Mondal, Partha Protim; Haldar, Purba; Ray, Amit; Bera, Malay Kumar (Asian Journal of Medical Sciences, 2022)
Background: Retrocaval ureter (RCU) is a rare congenital anomaly. It occurs due to anomalous development of inferior vena cava (IVC) and not ureter. Here, we describe our experience in surgical techniques and operative results of laparoscopic reconstruction for patients with RCU. Aims and Objectives: The aims of this study were to obtain information regarding clinical presentation, demographic profiles, investigations, indications for intervention, postoperative complications of laparoscopic repair of retrocaval repair, and also to develop laparoscopic surgical skill without causing any untoward effects to the patients. Materials and Methods: Twelve patients with RCU were enrolled in this study. The mean age was 32.4-years-old (23–37 years). All patients were preoperatively evaluated with different relevant imaging modalities. Laparoscopic surgery with transperitoneal approach with insertion of double-j stent was performed to all patients by same surgeon without excision of compressed ureter. Post-operative follow-up was done with ultrasonography every 3 months and repeat DTPA renogram every 6 months for 2.4 years. Results: All operations were completed laparoscopically without conversion to open surgery. There was no obstruction or symptom after the mean follow-up of 2.4 years. Conclusion: Transperitoneal laparoscopic repair is a feasible, safe, and effective modality of The treatment for RCU. Careful dissection along the planes with good respect to tissue and proper hemostasis during each step is the key to success for laparoscopic repair of RCU.